Breastfeeding: Intelligent Decision, Multiple Benefits And Protected Future - Dávila-Aliaga, Carmen Rosa (2017)
The best food for the newborn is breast milk, given the evidence of short and long-term medical and neurodevelopmentalbenefits. It should be considered a public health strategy to reduce neonatal morbidity and mortality, improve quality of lifein short and long term. Breast milk, also known as white blood, consists of approximately 258 components, from living cells,macro and micronutrients, hormones, defense system molecules, immunoglobulins, bacterias, etc; has great variability inrelation to the moment within the breastfeeding, time of day, age of the baby, according to the needs of the baby amongothers. The advantages extend to the mother and are multiple. For those cases where it is impossible to get breast milk, wemust be able to offer the option of receiving pasteurized milk from a milk bank. Currently the Ministry of Health and healthinstitutions have been working to accredit as a hospital friend of the mother and child, ensuring compliance with the 10 stepsfor successful breastfeeding, encouraging and supporting breastfeeding.